PilA localization affects extracellular polysaccharide production and fruiting body formation in Myxococcus xanthus - Yang, Zhe (2010)
Myxococcus xanthus is a gram-negative bacterium capable of complex developmental processes involving vegetative swarming and fruiting body formation. Social (S-) gliding motility, one of the two motility systems employed by M. xanthus, requires at least two cell surface structures: type IV pili (TFP) and extracellular polysaccharides (EPS). Extended TFP which are composed of thousands of copies of PilA retract upon binding to EPS and thereby pull the cell forward. TFP also act as external sensor to regulate EPS production. In this study, we generated a random PilA mutant library and identified one derivative, SW1066, which completely failed to undergo developmental processes. Detailed characterization revealed that SW1066 produced very little EPS but wild-type amounts of PilA. These mutated PilA subunits, however, are unable to assemble into functional TFP despite their ability to localize to the membrane. By preventing the mutated PilA of SW1066 to translocate from the cytoplasm to the membrane, fruiting body formation and EPS production was restored to the levels observed in mutant strains lacking PilA. This apparent connection between PilA membrane accumulation and reduction in surface EPS implies that specific cellular PilA localization are required to maintain the EPS level necessary to sustain normal S-motilityin M. xanthus.